Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1097/ta.0b013e3181f41af8
|View full text |Cite
|
Sign up to set email alerts
|

Normal Presenting Vital Signs Are Unreliable in Geriatric Blunt Trauma Victims

Abstract: Vital signs on presentation are less predictive of mortality in geriatric blunt trauma victims. Geriatric blunt trauma patients warrant increased vigilance despite normal vital signs on presentation. New trauma triage set points of HR >90 or SBP <110 mm Hg should be considered in the geriatric blunt trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(113 citation statements)
references
References 18 publications
5
99
0
7
Order By: Relevance
“…While the cut-points we identified in SBP were similar to those proposed in other studies, 31,33 the yield of such triage revisions appeared small. The lack of predictive value of SBP and heart rate among injured older adults has been previously demonstrated.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…While the cut-points we identified in SBP were similar to those proposed in other studies, 31,33 the yield of such triage revisions appeared small. The lack of predictive value of SBP and heart rate among injured older adults has been previously demonstrated.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies on this topic are limited by the use of hospital-based physiologic data, single-center trauma registries, exclusion of certain types of patients (e.g., penetrating injury, traumatic brain injury), and use of mortality as the primary outcome. 3033 Each of these factors introduces bias and reduces the ability to extrapolate findings to the out-of-hospital setting. We undertook the current study to help fill this void and better inform the next revision of the national field triage guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients are also more likely to have more co-morbidities and use of anticoagulants and/or antiplatelet agents (20% vs. 1% in this study). It has also been well established that elderly patients have decreased physiologic reserve and present with less reliable vital signs [26, 37]. Despite normal admission vitals, elderly patients are more prone to decompensation over time; clinicians may therefore more aggressively resuscitate these patients, particularly in the period before internal bleeding has been reliably excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, our study aimed to determine how age impacts blood transfusion during trauma resuscitations. It has been shown that geriatric trauma patients tend to be under-triaged, but what is unclear is whether they are under-resuscitated or over-resuscitated, given misleading vital signs secondary to pre-existing medical conditions and medication use [26]. Second, we hypothesized that the acute coagulopathy of trauma varies with age.…”
Section: Introductionmentioning
confidence: 99%
“…This type of accident is traditionally considered a minor mechanism of injury and deemed not to necessitate transfer to a trauma centre. However, many of these patients can sustain severe multisystem injuries, even if initially appearing stable [2, 3]. The combination of a greater likelihood of extensive medical comorbidities and a difficult, less-thorough assessment means that elderly trauma victims have significantly worse outcomes compared to their younger counterparts [4].…”
Section: Introductionmentioning
confidence: 99%